2021
DOI: 10.4236/psych.2021.123028
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Aspects of Worry among Younger and Older Adults: A Multifaceted Approach

Abstract: The aims of this study were to examine age-differences regarding various worry components among younger and older adults and to characterize the relationships between worry domains and anxiety. A total of 311 younger adults (18 -30 years) and 100 older adults (65+ years) completed seven worry and anxiety questionnaires, focusing on worry content, worry severity, and responses to worry. A series of 2 × 2 ANOVAs was computed to examine differences in worry and anxiety related to age and gender. Interaction effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Regarding age, our results showed that younger participants were more concerned than older participants. Previous studies have shown that worry regarding personal matters decreases with age [ 46 , 47 ]; while we evaluated other people’s risk and not personal risk, the same direction was maintained. There were also differences by region, the largest being between Northern and Eastern Europe.…”
Section: Discussionmentioning
confidence: 88%
“…Regarding age, our results showed that younger participants were more concerned than older participants. Previous studies have shown that worry regarding personal matters decreases with age [ 46 , 47 ]; while we evaluated other people’s risk and not personal risk, the same direction was maintained. There were also differences by region, the largest being between Northern and Eastern Europe.…”
Section: Discussionmentioning
confidence: 88%